2005
DOI: 10.1104/pp.104.056317
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of N2 Fixation in Soybean Is Associated with Elevated Ureides and Amino Acids

Abstract: Decreased N 2 fixation in soybean (Glycine max) L. Merr. during water deficits has been associated with increases in ureides and free amino acids in plant tissues, indicating a potential feedback inhibition by these compounds in response to drought. We evaluated concentrations of ureides and amino acids in leaf and nodule tissue and the concurrent change in N 2 fixation in response to exogenous ureides and soil-water treatments for the cultivars Jackson and KS4895. Exogenous ureides applied to the soil and wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
139
1
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(152 citation statements)
references
References 37 publications
7
139
1
5
Order By: Relevance
“…Entretanto, esses compostos vêm sendo detectados em plantas não leguminosas e sua produção pode estar relacionada à degradação de purinas, como relatado por Todd et al (2006). Adicionalmente, o acúmulo desses compostos pode estar diretamente relacionada a aquisição de tolerância em situações estressantes, como tem sido reportado por alguns autores (SINCLAIR et al, 2003;PURCELL et al, 2004;KING;PURCELL, 2005 …”
Section: Resultsunclassified
“…Entretanto, esses compostos vêm sendo detectados em plantas não leguminosas e sua produção pode estar relacionada à degradação de purinas, como relatado por Todd et al (2006). Adicionalmente, o acúmulo desses compostos pode estar diretamente relacionada a aquisição de tolerância em situações estressantes, como tem sido reportado por alguns autores (SINCLAIR et al, 2003;PURCELL et al, 2004;KING;PURCELL, 2005 …”
Section: Resultsunclassified
“…This indicated that the pesticides impose stress on ureide metabolism at higher doses. However the ureide levels have been shown to rise under water stress conditions also, and it has been suggested that the accumulation of ureides responsible for the feedback inhibition of nitrogen fixation in adverse conditions [32,33]. Recently reported that ureide content increases considerably in nonnodulated common bean plants suffering water stress and drought-induced senescence was considered the possible source of ureides [5].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of drought on traits related to BNF have been widely studied (King & Purcell, 2005;Hungria et al, 2006;Sinclair et al, 2007;Cerezini et al, 2014). However, despite some works on cotton, flowers, and fruits (Serek et al, 2006;De Pietro et al, 2010;Chen et al, 2015;Li et al, 2016), there is no knowledge of researches on the effect of 1-MCP on soybean, aiming to the attenuate negative effects of ethylene induced by drought stress on plant senescence, including nodules.…”
Section: Variables/ Treatmentsmentioning
confidence: 99%
“…(2) CV (%), coefficient of variation and p-value for water condition (W=), 1-MCP (M=), and WxM=. Purcell, 2005). Sinclair et al (2007) found differences between genotypes exposed to drought regarding N concentration in leaves.…”
Section: Variables/ Treatmentsmentioning
confidence: 99%